The impact of the quality of electronic banking services on customer satisfaction in Libyan commercial banks A field study on customers of Al-Wahda Bank, Sirte University branch (Economic studies journal, 2024)
This study aimed to identify the quality of electronic banking services in its dimensions (ease of use, time saving and responsiveness, confidentiality and security) and its impact on customer satisfaction at Wahda Bank, Sirte University branch. The researchers developed a questionnaire form to collect data that included (96) participants from the study community. The study has reached a set of results. The most important of which are: The level of quality of electronic banking was high and that there is a statistically significant impact of the dimensions (ease of use, time and speed of response, confidentiality and security) on customer satisfaction. The study recommended that, the bank's management should work on developing and improving the technology used, and finding ways to make better use of it, as the presence of advanced technology and trained and professional human elements would enhance the bank's performance, and customer satisfaction. In addition to collecting customer complaints, dealing with them quickly. Moreover, responding to their inquiries, and take their opinions regarding electronic banking services.
Keywords: Quality of banking services; customer satisfaction; electronic services; ease of use; time saving; and security; confidentiality